2012
DOI: 10.3109/01902148.2011.644027
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory stimuli up-regulate transient receptor potential vanilloid-1 expression in human bronchial fibroblasts

Abstract: Lung fibroblasts are involved in interstitial lung disease, chronic asthma, and chronic obstructive pulmonary disease (COPD). The expanded fibroblast population in airway disease leads to airway remodeling and contributes to the inflammatory process seen in these diseases. The cation channel transient receptor potential vanilloid-1 (TRPV1) is activated by noxious stimuli, including capsaicin, protons, and high temperatures and is thought to have a role in inflammation. Although TRPV1 expression is primarily re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 24 publications
0
28
0
1
Order By: Relevance
“…In the lung, TRPV1 expression has been found in human bronchial epithelial cells with an increase in expression in cells from the airways of patients with refractory asthma [99][100][101][102][103][104][105]109], fibroblasts [102], T-cells [106,107,115] and human alveolar macrophages [99]. Several studies suggest that TRPV1 channel activation evokes the release of proinflammatory cytokines and ATP from bronchial epithelial cells [99,[103][104][105]116].…”
Section: Trpv1mentioning
confidence: 99%
See 1 more Smart Citation
“…In the lung, TRPV1 expression has been found in human bronchial epithelial cells with an increase in expression in cells from the airways of patients with refractory asthma [99][100][101][102][103][104][105]109], fibroblasts [102], T-cells [106,107,115] and human alveolar macrophages [99]. Several studies suggest that TRPV1 channel activation evokes the release of proinflammatory cytokines and ATP from bronchial epithelial cells [99,[103][104][105]116].…”
Section: Trpv1mentioning
confidence: 99%
“…Given the emergence of potent TRPV1 inhibitors with appropriate pharmacokinetic profiles for in vivo studies the picture should become clearer in the future [11]. In the absence of definitive preclinical data, there are data available from human in vitro studies where increased TRPV1 gene expression has been demonstrated in asthma [100,102], and population-based genetic association studies which have documented a TRPV1 genetic variant to be associated with a lower risk of childhood asthma or the presence of wheezing [123].…”
Section: Trpv1mentioning
confidence: 99%
“…The transient receptor potential vanilloid 1 (TRPV1) 3 is a member of the TRP channel family of ion channels that has been widely associated with painful processes such as angina pectoris, arthritis, and cancer, as well as inflammatory events (1)(2)(3)(4)(5). The activation of this receptor in the peripheral sensory cells where it is expressed leads to pain perception (6,7).…”
mentioning
confidence: 99%
“…LPA has been importantly linked to neuropathic pain, and for several years it was thought to produce it solely through its interaction with specific GPCRs (LPA [1][2][3][4][5][6] ) (12,13), with the LPA 1 receptor being particularly important in this process (14). Recently, our group demonstrated a direct and physiologically relevant interaction of TRPV1 with LPA.…”
mentioning
confidence: 99%
“…Есть мнение, что у лиц с ХК увеличивается количество рецепторов TRPV1 в подслизистом слое ДП [10]. Кроме того, функ ция этих рецепторов стимулируется воспалитель ными медиаторами [11]. В экспериментальных исследованиях in vitro показано, что риновирус поражает нейроны человека и активирует TRPV1 и TRPA1 рецепторы [8].…”
Section: патогенез кашлевой гиперчувствительностиunclassified